Anti-PD-1 exacerbates bleomycin-induced lung injury in mice via Caspase-3/GSDME-mediated pyroptosis - Fei Wang; Haiyi Deng; Maolin Zhou; Yilin Yang; Jiankui Zhou; Yansheng Wang; Xiaohong Xie; Xinqing Lin; Ming Liu; Gengyun Sun; Chengzhi Zhou (Cell Death and Disease)
Abstract Immune checkpoint inhibitors (ICIs) have significant therapeutic effects but can also cause fatal lung injury. However, the lack of mouse animal models of ICI-related lung injury (ICI-LI) has limited the in-depth exploration of its pathogenesis. In clinical practice, underlying lung diseases increase the risk of lung injury. Thus, we used a mouse model of lung injury induced by bleomycin (BLM) and then administered anti-programmed cell death 1 (aPD-1) antibodies to induce ICI-LI. Compared with the BLM group, the aPD-1 + BLM group presented more significant weight loss, greater levels of lung inflammation and fibrosis, and decreased lung function. In this ICI-LI model, high levels of caspase-3/gasdermin E (GSDME) were detected in the lung tissue of mice, and the JNK inhibitor SP600125 mitigated lung damage by inhibiting GSDME-mediated pyroptosis. Consistent with the findings in the animal model, immunofluorescence and RNA sequencing of lung tissue from ICI-LI patients revealed upregulation of the expression of genes related to the GSDME-related pyroptosis pathway. Our results suggest that GSDME-mediated pyroptosis may be associated with the pathogenesis of ICI-LI, indicating that targeting GSDME could be a potential therapeutic strategy for treating ICI-LI.